Minimum Water Requirement Method for High-Performance Sulphoaluminate Cement-Based Materials - Hong-ping Zhang; Pei-kang Bai; Jian-hong Wang; Yan-li Dong; Yun-shan Han (Advances in Materials Science and Engineering)
In this work, we propose the use of steel slag instead of slag powder, in addition to fly ash and silica fume, to obtain high-performance sulphoaluminate cement-based materials. According to the closest-packing theory and on the basis of the minimum water requirement test, the influence of mineral admixtures on the minimum water requirement was evaluated for sulphoaluminate composite system paste. The optimal composition of the cementitious materials was thus determined. Orthogonal tests were used to assess the validity of this ratio. The correlation between minimum water requirement and the standard consistence was not only analyzed in the system of the minimum water requirement method decided but also in the complicate system of the orthogonal tests determined. Experimental results show that the influence of steel slag on the minimum water requirement is the largest in composite cement paste; minimum water requirement and standard consistency have a good correlation; the cement paste designed with the optimum composite had the highest strength of all the tested materials, but minimum water requirement and strength have a poor correlation in the orthogonal tests. We demonstrate that standard consistency evaluation can replace the minimum water requirement method to determine the optimum ratio of cement mineral admixtures. The proposed method not only simplifies the process but also makes the method more scientific.